New C-3 Substituted 1H- and 2H-Indazolephosphonic Acid Regioisomers: Synthesis, Spectroscopic Characterization and X-Ray Diffraction Studies - Teixeira, António P.S. (2021)
Indazole is known as an important structural motif in medicinal chemistry and, recently, has also gained attention in other areas, such as materials chemistry, with many studies showing different potential applications for their regioisomers. Phosphonates are also a class of compounds with diverse applications, ranging from medicinal to material applications. Here we present the synthesis of 1H- and 2H-indazolephosphonic acid derivatives substituted at C-3, involving mono- or bisphosphonic acids, from their corresponding carboxylic acid and esters. These compounds were fully characterized, and their spectroscopic data were evaluated to identify and distinguish the structural scaffold of each phosphonic acid. Crystallization of [hydroxy(1-methyl-1H-indazol-3-yl)methanediyl]bis (phosphonic acid) 7 afforded crystals suitable for single crystal X-ray diffraction studies and its crystal structure details are also discussed.